Towards an Abrahamic ecumenism? The search for the universality of the divine mystery - C. van der Kooi (Acta Theologica)
This contribution explores the notion of an Abrahamic ecumenism as proposed by Hans Küng and others in search for a way in which Islam, Judaism and Christianity can live peacefully together. It is argued, however, that to pursue a viable political pluralism, it is more promising for Christian theology to take into account the historical development of the image of God instead of an orientation on a common historical origin in Abraham. The elaboration of the universality of the divine mystery in history does not have to be won by going back to Abraham, but by going forward to Jesus Christ and by thinking of and living out of Him.